Family-to-work spillover effects of family incivility on employee sabotage in the service industry. Issue 2 (8th April 2019) - Cheng, Bao; Zhou, Xing; Guo, Gongxing
Abstract : Purpose: This study aims to explore family incivility as a source of stress originating in the family domain and empirically examine its spillover effects on the workplace. Design/methodology/approach: Through integrating the work–family interface model with conservation of resources (COR) theory, this study investigated the effect of family incivility as perceived by employees of the service industry on service sabotage, along with the mediating role of family-to-work conflict (FWC) and the moderating role of work–family centrality. Findings: The results of a three-wave survey of 335 employees in China and 62 of their immediate supervisors demonstrated that family incivility was positively related to service sabotage, and FWC also mediated this relationship. Moreover, work–family centrality was found to strengthen the effect of family incivility on FWC, as well as the mediating effect of FWC on the relationship between family incivility and service sabotage. Research limitations/implications: This study not only enriched the work–family interface literature but also suggested new insights into sabotage behaviors by focusing on antecedents in the family domain. Practical implications: By realizing that family incivility has detrimental effects on service employee behaviors, enterprises and managers should provide greater support for employees in managing family incivility and help them to maintain a better balance between work and family life. Originality/value: This study appears to be the first empirical evidence linking a family stressor (i.e. family incivility) with a workplace behavioral outcome in the service industry (i.e. service sabotage).